Beyond the classroom: a phenomenological inquiry into the challenges of English language learning for non-ELT students at UII DALWA - Kuzairi Kuzairi (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2025)
This study investigates the challenges of English learning faced by non-ELT students at Universitas Islam Internasional Darullughah Wadda'wah (UII DALWA). Situated in a unique trilingual environment dominated by Arabic and Indonesian, these students encounter distinct barriers. Through unstructured interviews with 20 participants from various non-ELT programs, the research identifies and categorizes these challenges into four main areas. The findings indicate that Linguistic-Cognitive Difficulties, such as limited vocabulary, grammar anxiety, and pronunciation issues, are the most prevalent challenges. These are closely followed by Affective-Psychological Barriers, including anxiety and fear of making mistakes. Furthermore, Socio-Cultural and Motivational Factors, such as perceiving English as irrelevant to Islamic identity, and Contextual-Environmental Constraints, like limited exposure and practice opportunities, significantly hinder proficiency. The study concludes that these challenges are deeply interconnected, creating a cyclical barrier to language acquisition. It recommends developing tailored pedagogical strategies that integrate Islamic content to boost motivation and address the specific needs of this student population, suggesting avenues for further research into effective interventions.